Pembelajaran Kitab Kuning pada Pondok Pesantren Khusus Al-Halimy Desa Sesela Kabupaten Lombok Barat - Ar Rasikh Ar Rasikh (Universitas Islam Negeri (UIN) Mataram, 2018)
Kitab kuning merupakan faktor penting yang menjadi karakteristik Pondok Pesantren (Ponpes). Artikel ini membahas pembelajaran Kitab Kuning di Pondok Khusus Ponpes Al-Halimy Sesela. Pembahasan difokuskan pada metode dan penerapannya dalam pembelajaran, serta teknik penilaian setelah pelakasanaan pembelajaran berlangsung. Hasil penelitian menunjukkan bahwa Pondok Khusus Al-Halimy Sesela menerapkan beberapa metode yang lazimnya digunakan di pondok-pondok Salaf, menggunakan metode klasik, yaitu metode sorogan, bandongan, wetonan, halaqoh, diskusi, demonstrasi, dan tanya jawab. Penerapan metode-metode dalam pembelajaran kitab kuning didasarkan kesesuaian metode yang akan digunakan dengan mata pelajaran yang akan diajarkan. Keberhasilan suatu metode yang diterapkan dalam pembelajaran kitab kuning di Pondok Khusus Al-Halimy Sesela diukur dengan menggunakan beberapa cara di antaranya adalah dengan menguji secara langsung. Hendaknya tradisi pesantren Salaf tetap dapat dipertahankan dan selanjutnya memasukkan tradisi pesantren khalaf yang lebih baik, pemilihan metode yang tepat guna supaya memberikan dampak positif bagi kemajuan pendidikan pesantren sehingga akan muncul lulusan-lulusan yang betul-betul tafaqquh fi al-din. Title: Learning of Kitab Kuning “Yellow Book” at Special Al-Halimy Islamic Boarding School In Sesela Village of West Lombok Regency Abstract: The yellow book is an important factor which becomes characteristic of Islamic Boarding Schools. The results of the preliminary research showed that the Special Al-Halimy Islamic Boarding School of Sesela only studies classical books or yellow books which are not included in the governmental curriculum. The focuses of the study in this research included: First, it is related to the method used in yellow book learning; Second, it is related to how the application of learning methods is; Third, it is related to how the assessment after the implementation of yellow book learning takes place. The research design used descriptive qualitative. Then the results of the research showed that 1) special Al-Halimy Islamic Boarding School of Sesela applies several methods commonly used in Salaf Islamic Boarding Schools which teach yellow books, such as sorogan (individual), wetonan (group), and discussion methods. In addition, the types of methods used still use classical methods, namely the sorogan, bandongan, wetonan, and halaqoh methods, and also there are discussion, demonstration and question and answer methods, 2). The application of methods in yellow book learning is based on the suitability of method to be used with the subjects to be taught. 3). To find out the success level of a method applied in the yellow book learning at special Al-Halimy Islamic Boarding School of Sesela is by using several methods including testing directly. The final advice is given to the head of the Special Islamic Boarding School in order to maintain the tradition of the salaf Islamic Boarding School and incorporate the tradition of a better Khalaf Islamic Boarding School in order to give a positive impact on the progress of Islamic Boarding School education so that the graduates who truly understand the religion (tafaqquh fi al-din) will emerge and for the teachers of special Al-Halimy Islamic Boarding School of Sesela, they have to be able to choose the right learning method and be able to see what the students need in joining the learning so that the learning objectives can be achieved.